106k views
5 votes
If f(x) = 2x – 1 and g(x) = – 2, find [g ◦ f](x).

2 Answers

1 vote

Answer:

[g ◦ f](x)=-2

Explanation:

f(x) = 2x – 1

g(x) = – 2

[g ◦ f](x)

This is a composite function. It means we take f(x) and substitute it in for x in the function g(x)

g(x) = -2

There is no x in the function, so g(x) remains the same

[g ◦ f](x)= -2

User Binder
by
4.7k points
7 votes

Answer:

Explanation:

Wherever you see an x in g(x) you are supposed to put f(x).

If g(x) = x

then

g(f(x)) = f(x)

g(x) = f(x)

Since g(x) has no xs, then g(f(x)) = - 2

g(x) = -2 no matter what x is in g(x)

g(2x - 1) = - 2

User Navin Bista
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.